Development and validation of a HPLC with fluorescence detection method to quantify the peanut allergen Ara h 2 in peanut extract and sublingual films. Issue 9 (13th September 2018) - Jiang, Bowen; Ibrahim, Ahmed; Martin, Russell; Keet, Corinne; Mao, Hai‐Quan; Hoag, Stephen W.
Abstract: A rapid and selective reversed‐phase high‐performance liquid chromatographic method with fluorescence detection was developed for quantitation of the peanut allergen Ara h 2 in peanut extracts and dissolving sublingual films containing peanut extracts. The separation of Ara h 2 from other proteins in the peanut extracts and dosage matrix is a challenging problem, and the separation was optimized using DryLab ® software. The high‐performance liquid chromatography method involved a BEH C4 Column running at 52°C for 25 min, with a gradient elution of acetonitrile and water containing 0.1% trifluoroacetic acid. Fluorescence detection was used at an excitation wavelength of 261 nm and emission wavelength of 310 nm. The linearity range was 7.5 to 30 μg/mL, with a calculated detection limit of 1.61 μg/mL and a quantitation limit of 4.89 μg/mL. The validated method was applied to quantitate the amount of Ara h 2 in the sublingual films containing peanut extract, which was designed to desensitize children with peanut allergy. This method was also used to evaluate the accelerated stability of five different formulations of sublingual films and was able to distinguish differences among formulations.